The phenomenology of tourism space - Kowalczyk, Andrzej (Turyzm/Tourism, 2014)
Although it is among the most frequently used notions in the study of tourism, the concept of tourism space is understood in a variety of ways. Similar to the term ‘geographical space’, it is often used intuitively, often in quite dissimilar contexts. This paper provides an analysis of the concept of ‘tourism space’ from the perspective of geography, based on a phenomenological approach.